Afetividade e educação: a relação professor-aluno e o processo de ensino aprendizagem - Gomes, Amanda Carvalho (Brasil, 2024)
The present work aims to understand the importance of affectivity for the teaching-learning process, as well as analyze affectivity in the teacher-student relationship and its importance for the teacher's work, identify affectivity in the family and school relationship and highlight how teachers of an elementary school relate affectivity in daily school life. From the experiences during the Supervised Internship discipline in the Pedagogy course at the Institute of Social Sciences, Education and Animal Science-ICSEZ-UFAM, it was noticed that teachers and future educators little understand the importance of affection in the teacher-student relationship and how this relationship can influence teaching-learning. The theoretical contribution is based on studies on affectivity, teaching and learning, especially considering the perspective of Henri Wallon (1975), among other authors who research on the proposed theme. In methodological terms, this is research with a qualitative approach and field research. The data collection process consisted of three stages: first, bibliographic research, second, field research and third, descriptive analysis. Interviews, a semi-structured questionnaire were used as data collection instruments, as well as field research. Qualitative research is configured, based on Denzin and Lincoln (2006), in the interpretation of reality, making it possible to use interviews as a research technique. The universe studied was designed with three first-year elementary school classes at a public school in the city of Barreirinha-AM, totaling 78 students. Observation was carried out in the school context and interviews were carried out with three elementary school teachers. The descriptive analysis of the data shows that it is possible to affirm the importance of affectivity for the teaching-learning process and for the formation of critical citizens who will be active in society in the future, with the school, teachers and family as an indispensable set for the good educational development of the community. student.